Effects of toothed edges and window openings on seismic behaviour of confined masonry walls - Lim, Namyo Salim (2022)
Confined masonry (CM) structures have been widely adopted by many developing countries located in seismically active regions due to their satisfactory seismic performances, cost-effectiveness and ease of construction; for example, the construction of CM structures in Nepal after the 2015 earthquake by Smart Shelter Foundation (SSF) to provide affordable structures with reliable seismic performance. However, as CM is a much less researched topic compared to other types of structures, some of the design provisions from codes and practices adopted by SSF for their CM structures are ambiguous or even appear contradictory. Hence, the research presented in this paper has been conducted in response to SSF's request to investigate the effectiveness of the adopted design and construction methods of their CM structures. In the experiment, three CM specimens constructed following the design provided by SSF was subjected to in-plane cyclic loading with two cycles per drift at 1.0% increment until a 20% drop in maximum strength was attained to investigate the effectiveness of toothed wall-to-column connections and effects of a window opening in the masonry panel. Toothed wall-to-column connections may not provide significant improvement to the in-plane seismic response, but provision of a lintel band above an opening can alleviate the detrimental effect.